U. S. Turns to South America for Many Critical Minerals - AIME AIME (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1942)
MICA is perhaps our No. 1. strategic mineral problem because of its large requirements in a variety of equipment for use in the military services, and because the principal source of this material has heretofore been British India, a source now threatened partly because of distance and lack of ships. [Block mica and bauxite were added to the "most critical" list published by the W.P.B. on Nov. 6.] No satisfactory substitute has yet been found for most of the uses of mica, which largely involve electrical insulation. Brazil is now our nearest and best major source of this material. No splitting plants have yet been established there but in 1941 we imported about a million pounds of block mica from that country and in 1942 that quantity will be considerably exceeded. In Brazil, mica is found almost exclusively in the pegmatite dikes along the mountain range bordering the eastern part of Minas Gerais. A belt, roughly 180 miles long by 100 miles wide, extends from Theophilo Ottoni to Carangolo. The principal mica-mining districts in this belt are the Governador Valladares area to the north and the Espera Feliz district to the south. The dikes are usually 10 to 50 meters wide and a mile or two long and intrude the old metamorphic schist formation. They are weathered and easily mined.